THE EFFECTIVENESS OF USING SCREENS ON COMPUTER MONITORS AGAINST EYE MUSCLE FATIGUE OF EMPLOYEES AT THE AMBON CITY EDUCATION OFFICE IN 2023 - Gherice E. Serumena; Aragar Putri; Abdul Baktiansyah; Triana Srisantyorini; Syamsiar S. Russeng (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Eye fatigue is a somatic disorder in the ciliary muscle of the eye that is forced to work to see close objects for long periods of time. Computers as electronic devices use electrical energy and electromagnetic radiation waves that are harmful to eye health. The installation of Antiglare Screen on a computer monitor is believed to reduce complaints of eye muscle fatigue so it needs to be reviewed for the effectiveness of its use. It is known the effectiveness of using screens on computer monitors to reduce eye muscle fatigue of employees at the Ambon City Education Office in 2023. Quantitative research design with quasy experiment method. Using Simple Random Sampling technique as many as 30 respondents. Data collection techniques using questionnaires and interventions using screen monitors measured by the photostress recovery test method. The measurement results are analyzed by the repeated-measured anova statistical test. The average prevalence value of eye muscle fatigue ≥ 50 seconds before the screen installation intervention on a computer monitor. After the intervention, post-measurement of 1 right eye on the fourth day amounted to 14.833 seconds, the OR value was 0.028, for the left eye it was 14.633 seconds, the OR value was 0.001. Post measurement-2 of the right eye on the sixth day of 26.367 seconds of OR value of 0.026, for the left eye of 25.533 seconds OR value 0.016. Furthermore, Post measurement-3 right eye on day 10 amounted to 35,200 seconds OR value -0.001, for left eye 35,700 seconds OR value -0.038. There was a difference in the average fatigue of the eye muscles in three post-measurements using the photostress recovery test method. Post-measurement variable-3 on day 10 of the intervention using a computer monitor screen had an effect on reducing eye muscle fatigue. The longer respondents use antiglare screen, the less eye muscle fatigue. Although there were respondents who had refractive errors, the use of screen monitors was effective in reducing fatigue of the right eye OR (-0.001) and left eye OR (-0.038). Computer users must have occupational safety and health awareness in using computers. Pay attention to the arrangement of the workspace and optimize eye rest time by occasionally turning your eyes to the green area filled with trees outdoors.